How to manage patellofemoral pain – Understanding the multifactorial nature and treatment options. (July 2018) - Lack, Simon; Neal, Bradley; De Oliveira Silva, Danilo; Barton, Christian
Abstract: Patellofemoral pain (PFP) is one of the most prevalent conditions within sports medicine, orthopaedic and general practice settings. Long-term treatment outcomes are poor, with estimates that more than 50% of people with the condition will report symptoms beyond 5 years following diagnosis. Additionally, emerging evidence indicates that PFP may be on a continuum with patellofemoral osteoarthritis. Consensus of world leading clinicians and academics highlights the potential benefit of delivering tailored interventions, specific to an individual's needs, to improve patient outcome. This clinical masterclass aims to develop the reader's understanding of PFP aetiology, inform clinical assessment and increase knowledge regarding individually tailored treatment approaches. It offers practical application guidance, and additional resources, that can positively impact clinical practice. Highlights: Altered biomechanics, tissue homeostasis, structure and non-mechanical factors may all contribute to PFP symptoms and persistence. A multidimensional assessment, using reflective questioning, should be adopted to ensure the development of an appropriately targeted and individualised management plan. Exercise therapy should incorporate both proximal and local components. Movement retraining should be delivered on an individual basis, and can be valuable during pain provocative tasks e.g. stairs. Tailored patella taping and foot orthoses should be considered to modify pain and promote function. Patient education should form an integral part of your management approach.